2010
DOI: 10.21273/hortsci.45.9.1327
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical String Thinner Reduces Crop Load at Variable Stages of Bloom Development of Peach and Nectarine Trees

Abstract: Thinning of blossoms or fruitlets is a labor-intensive requirement in the production of peach and nectarine (Prunus persica) fruit of optimum size and quality. Prior research conducted by the authors on string blossom thinners for managing peach tree crop load demonstrated that this new technology reduces labor requirement and improves fruit size. The research reported in the current article was conducted over 2 years on ‘Sugar Giant’ peach and ‘Arctic Sweet’ nectarine to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The impracticality and cost of HBT and the inconsistent performance of chemical thinners has spurred interest in mechanical blossom thinning. Several machines based on rotating brushes, strings or ropes have decreased fruit set, reduced the time needed for hand thinning and increased the proportion of fruit in large size categories in tests on several tree fruit species (Schupp et al 2008;Weibel et al 2008;Damerow and Blanke 2009;Auxt Baugher et al 2010). Peach and nectarine seem especially amenable because they bear single flowers on 1-yr-old wood (Schupp et al 2008;Auxt Baugher et al 2010;Miller et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impracticality and cost of HBT and the inconsistent performance of chemical thinners has spurred interest in mechanical blossom thinning. Several machines based on rotating brushes, strings or ropes have decreased fruit set, reduced the time needed for hand thinning and increased the proportion of fruit in large size categories in tests on several tree fruit species (Schupp et al 2008;Weibel et al 2008;Damerow and Blanke 2009;Auxt Baugher et al 2010). Peach and nectarine seem especially amenable because they bear single flowers on 1-yr-old wood (Schupp et al 2008;Auxt Baugher et al 2010;Miller et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several machines based on rotating brushes, strings or ropes have decreased fruit set, reduced the time needed for hand thinning and increased the proportion of fruit in large size categories in tests on several tree fruit species (Schupp et al 2008;Weibel et al 2008;Damerow and Blanke 2009;Auxt Baugher et al 2010). Peach and nectarine seem especially amenable because they bear single flowers on 1-yr-old wood (Schupp et al 2008;Auxt Baugher et al 2010;Miller et al 2011). In apple and pear, which have more complex flowering, mechanical thinning can damage spurs and shoots (Weibel et al 2008), and it significantly raises the risk of spreading fire blight (Ngugi and Schupp 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Uniform numbers of fruiting shoots were left in each treatment within a training system-60 in perpendicular V-trained trees and 125 in open center-trained trees. Based on earlier studies that determined optimum bloom stage for thinning, trees were mechanically thinned when 20% to 80% of the blossoms were open (Baugher et al, 2010b). Mechanically thinned pruning treatments were compared with green fruit hand-thinned (35 DAFB) control treatments on trees with standard pruning.…”
Section: Methodsmentioning
confidence: 99%
“…The next year, a string thinner was manufactured that operated in either a vertical or horizontal position, and trials conducted in four peachproducing regions on both narrow vertical and open-center canopies demonstrated reductions in follow-up hand-thinning requirement and increases in yield and fruit size (Baugher et al, 2010a). Pennsylvania trials conducted with the hybrid thinner on both perpendicular V-and open center-trained trees at various bloom stages showed that the window for thinning peach and nectarine trees ranges from the pink to the petal fall stage of bloom development (Baugher et al, 2010b).…”
mentioning
confidence: 99%
“…In addition, the effect of mechanical thinning is immediate and not influenced by climatic conditions (Martín et al, 2010). Inconsistent results, however, have hampered the successful implementation of mechanical thinning in stone fruit (Reighard and Byers, 2009 Schupp et al (2008) found added economic benefits in producing larger peach fruit while reducing follow-up hand thinning when they combined mechanical bloom thinning with green-fruit hand thinning (Miller et al, 2011;Baugher et al, 2009;Baugher et al, 2010;Schupp et al, 2008). The Darwinä does not thin selectively enough and will therefore not replace hand thinning completely (Miller et al, 2011).…”
mentioning
confidence: 99%